Defence tactic in volleyball: the analysis of the results of the pedagogic supervising. The competitive activity of the volleyball players - A A Lobanov; I A Demidkina; Y V Shikhovtsov (Peoples' Friendship University of Russia (RUDN University), 2009)
The article analyses the technical and tactical actions that are used by volleyball players of high qualification during the competition. Taking into account this information in the studying and training process contributes to the increase of its effectiveness.